2007
DOI: 10.1021/ic701670u
|View full text |Cite
|
Sign up to set email alerts
|

First-Row Transition Metal−Halide Complexes Supported by a Monoanionic [N2P2] Ligand

Abstract: Metal-halide complexes of a multidentate monoanionic ligand tBuN(H)SiMe2N(CH2CH2PiPr2)2, H[N2P2], with Ti, V, Cr, Mn, Fe, Co, and Ni have been isolated and characterized. X-ray crystallographic studies were performed on [N2P2]TiCl2 (3), [N2P2]CrCl2 (5), [N2P2]MnCl (6), [N2P2]FeCl (7), [N2P2]CoCl (8), and [N2P2]NiBr (9), and the results revealed that the [N2P2] ligand exhibits considerable flexibility in the manner in which it binds to first-row metals and that three distinct coordination modes are observed: ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 50 publications
4
28
1
Order By: Relevance
“…It suggests the former is much tighter than the latter. They are different from corresponding bond lengths 1.972 (4)Å and 2.356 (6)Å in a related amido Ti(III) compound reported by Chomitz et al (2008).…”
Section: S1 Commentcontrasting
confidence: 91%
See 2 more Smart Citations
“…It suggests the former is much tighter than the latter. They are different from corresponding bond lengths 1.972 (4)Å and 2.356 (6)Å in a related amido Ti(III) compound reported by Chomitz et al (2008).…”
Section: S1 Commentcontrasting
confidence: 91%
“…It is interesting that the valence of Ti has changed from IV to III. Similar situation could be found in Ovchinnikov's work (Ovchinnikov et al, 1993) and other - Chomitz et al, 2008). The driving factors for reduction will be investigated in further research.…”
Section: S1 Commentsupporting
confidence: 69%
See 1 more Smart Citation
“…[60][61][62] Given this precedence, a "mixed-donor" tri- . [63] All but the V analogue were structurally characterized, and one feature of these complexes that was revealed from the X-ray diffraction studies was the different coordination modes observed in the solid-state: k 3 -N 2 P, k 3 -NP 2 , and k 4 -N 2 P 2 . The electronic and geometric preferences of the metal center appear to dictate the coordination mode of the ligand with more electropositive metals such as Ti preferring coordination of the two harder nitrogen donors over the two phosphine donors (k 3 -N 2 P).…”
Section: "Mixed-donor" Tripodal Ligandsmentioning
confidence: 99%
“…Li[N 2 P 2 ] was shown to be a useful starting material for the synthesis of a wide range of first‐row transition‐metal compounds by means of salt metathesis reactions. The first‐row metal‐halide complexes [TiCl 2 (N 2 P 2 )], [VBr 2 (N 2 P 2 )], [CrCl 2 (N 2 P 2 )], [MnCl(N 2 P 2 )], [FeCl(N 2 P 2 )], [CoCl(N 2 P 2 )], and [NiBr(N 2 P 2 )] were synthesized and isolated in good yields following the reaction of the metal halide starting material [MX 3 (thf) 3 ] (M=Ti, V, Cr; X=Cl, Br) or MX 2 (M=Mn, Fe, Co, Ni; X=Cl, Br) with Li[N 2 P 2 ] 63. All but the V analogue were structurally characterized, and one feature of these complexes that was revealed from the X‐ray diffraction studies was the different coordination modes observed in the solid‐state: κ 3 ‐N 2 P, κ 3 ‐NP 2 , and κ 4 ‐N 2 P 2 .…”
Section: “Mixed‐donor” Tripodal Ligandsmentioning
confidence: 99%